PERAN PENGURUS ORGANISASI ASRAMA DALAM MELAKSANAKAN SOLIDARITAS ORGANIK ANTAR MAHASISWA DI ASRAMA - Artha, Candra Dwipa; Zakso, Amrazi; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine the Role of Boarding Organization Organizers in implementing Organic Solidarity among students in Kayong Putra Dormitory 1. The research method used is descriptive with qualitative research forms. The data source of this research is the Boarding Organization of Kayong Putra Dormitory 1. Data collection techniques in this study are through observation, interviews and documentation, while the data collection tools used are observation guides, interview guides and notebooks and archives. The analysis in this study was presented in a descriptive qualitative manner using four informants, consisting of the Chairperson and the secretariat of the board of the boarding organization and two students living in the dormitory. The results of this study indicate that, there is a division of labor and interdependence carried out by board members of the boarding organization. In the division of labor there are groupings of work and the close relationship of work, whereas in interdependence there are individuals who have different functions in the group and each individual has different specialties in the group.Â Keywords: Role, Organizational Management, Organic SolidarityÂ